Audio-Based Podcast Media to Improve Listening Skills on Transitive and Intransitive Sentences - Triana, Juli; Nugraheti Sismulyasih SB.; Panca Dewi P. (Journal of Education Reseach and Evaluation, 2024)
The lack of teacher innovation in providing learning media makes learning activities monotonous and boring. This research aims to develop audio-based podcast learning media for Indonesian language learning in grade IV elementary schools. The type of research used is research and development, which refers to the Borg and Gall model. Determination of media validity is carried out by validating media and material experts. The subjects of this research trial were teachers and students (small-scale trial with 6 students and large-scale trial with 24 students. The methods used to collect data were observation, interviews, questionnaires, documentation, and tests. The instruments used in collecting data were questionnaire sheets and test questions. The techniques used to analyse the data are qualitative descriptive analysis and quantitative and inferential statistics. The results of the research show that the assessment given by learning media experts is 91.7%, resulting in very decent qualifications 94%, resulting in a very decent qualification. The t-test results show that there is an increase in the average pre-test and post-test scores. The N-gain test results show a value of 0.73 on the small scale in the high category and a value of 0.61 on the large scale. medium category. It was concluded that audio-based podcast learning media was useful and effective in improving the learning outcomes of class IV students in transitive and intransitive sentence material.